2006
DOI: 10.1007/s10570-006-9069-9
|View full text |Cite
|
Sign up to set email alerts
|

Sorption studies on regenerated cellulosic fibers in salt–alkali mixtures

Abstract: The degrees of salt sorption were determined in lyocell and viscose fibers immersed in aqueous solutions of salt-alkali mixtures with the aim of using salt sorption as an indirect measure of changes to fiber accessibility in presence of alkali. The salt-alkali mixtures used were combinations of NaOH with NaCl or NaBr, and of KOH with KCl or KBr. In general, salt sorption in fibers increased with increase in alkali concentration up to 2 mol/l, and did not change significantly thereafter. The accessibility of Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
1
17
1
1
Order By: Relevance
“…Then the fibers were dried in room temperature followed by oven drying for 3 h at 105°C. Fiber behavior on alkali treatment was studied in previous research (Ramamoorthy et al 2014;Jaturapiree et al 2006;Okubayashi and Bechtold 2005).…”
Section: Alkali Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the fibers were dried in room temperature followed by oven drying for 3 h at 105°C. Fiber behavior on alkali treatment was studied in previous research (Ramamoorthy et al 2014;Jaturapiree et al 2006;Okubayashi and Bechtold 2005).…”
Section: Alkali Treatmentmentioning
confidence: 99%
“…Regenerated cellulose fibers are chemically pure, their surface structure is even, and the fiber properties can be reproduced easily (Woodings 2001;Carrillo et al 2010;Adusumali et al 2006;Fink et al 2014). It is also found that these fibers have good potential to be used as reinforcement in FRC (Carrillo et al 2010;Adusumali et al 2006;Ganster and Fink 2006;Jaturapiree et al 2006). High surface evenness and even quality of these fibers makes it possible to get consistent results which are not possible in natural fiber (Woodings 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with alkali can improve mechanical and chemical properties of cellulose fibres such as dimensional stability, fibrillation tendency, tensile strength, dyeability, reactivity, lustre and fabric smoothness. Factors such as the concentration of NaOH, treatment temperature, applied tension, residence time, source of cellulose, physical state of cellulose (fibril, fibre, yarn or fabric), and degree of polymerisation have an effect on the properties and degree of change upon treatment (Heinze and Wagenknecht 1998;Colom and Carrillo 2002;Jaturapiree et al 2006;Manian et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with alkali can improve mechanical and chemical properties of cellulose fibres such as dimensional stability, fibrillation tendency, dyeability, reactivity, lustre and fabric smoothness. Factors such as the concentration of NaOH, treatment temperature, applied tension, residence time, source of cellulose, physical state of cellulose (fibril, fibre, yarn or fabric), and degree of polymerisation have an effect on the properties and degree of change upon treatment (Heinze and Wagenknecht 1998;Colom and Carrillo 2002;Jaturapiree et al 2006;Manian et al 2008). In general, there is limited research in this area on cellulose II polymers; researchers have concluded that when cellulose I is converted to cellulose II the crystallinity index decreases, therefore, it is interesting to understand the change in crystallinity of cellulose II polymers when treated in alkali, particularly considering the increasing demand for lyocell fibres.…”
Section: Introductionmentioning
confidence: 99%